Morbidity and Long-Term Follow-Up in CDH Patients - Chiu, Priscilla P. L.; IJsselstijn, Hanneke (European Journal of Pediatric Surgery, 2012)
Overall survival of congenital diaphragmatic hernia (CDH) patients has increased since the widespread implementation of delayed operative repair with extracorporeal membrane oxygenation/gentle ventilation strategies starting in the mid-1990s. With the improvements in survival, CDH survivorship has been marked by increased morbidity with a greater need for monitoring and supportive interventions in infancy and early childhood. The multisystem morbidity and complexity of care for these patients mandate the dedicated resources and focus of medical specialties to ensure that the neurodevelopmental, cardiopulmonary, nutritional, and surgical sequelae of CDH are properly addressed. In this article, we will discuss the experience of CDH centers that offer long-term CDH follow-up as well as the patients' morbidities that require active monitoring until transition to adult care.
Keywords: congenital diaphragmatic hernia; follow-up; outcome